1992
DOI: 10.1139/v92-249
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Wittig reaction with cyclic anhydrides

Abstract: The reactions of stabilized phosphoranes with cyclic anhydrides give enol-lactones as final products. The initial condensation, however, leads to the formation of acyclic adducts that are observable by NMR, can be easily trapped, and, in some cases, can be isolated. A study of the mechanism of these condensations by NMR spectroscopic methods and by various trapping experiments is described and the reaction pathway is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Thus, Wittig reactions yielded exclusively E isomers, in 60 % yield when the reaction was carried out without a solvent20a or in 87 % yield after 18 h in chloroform at reflux 20b. Later, during a mechanistic study of this reaction, it was found that in chloroform at room temperature the E isomer was formed in 52 % yield along with a 13 % yield of the Z isomer 20c. Non‐cyclic anhydrides are known to react with stabilized phosphoranes to afford the acylation products, diketo phosphoranes,21 and the occurrence of the normal Wittig reaction and the exclusive or predominant formation of the E isomers with phthalic anhydride were explained in terms of formation of a π–π complex between the C=O group of the phosphorane and the electron‐deficient benzenic ring of phthalic anhydride 20a,20c,20d.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, Wittig reactions yielded exclusively E isomers, in 60 % yield when the reaction was carried out without a solvent20a or in 87 % yield after 18 h in chloroform at reflux 20b. Later, during a mechanistic study of this reaction, it was found that in chloroform at room temperature the E isomer was formed in 52 % yield along with a 13 % yield of the Z isomer 20c. Non‐cyclic anhydrides are known to react with stabilized phosphoranes to afford the acylation products, diketo phosphoranes,21 and the occurrence of the normal Wittig reaction and the exclusive or predominant formation of the E isomers with phthalic anhydride were explained in terms of formation of a π–π complex between the C=O group of the phosphorane and the electron‐deficient benzenic ring of phthalic anhydride 20a,20c,20d.…”
Section: Resultsmentioning
confidence: 98%
“…Later, during a mechanistic study of this reaction, it was found that in chloroform at room temperature the E isomer was formed in 52 % yield along with a 13 % yield of the Z isomer 20c. Non‐cyclic anhydrides are known to react with stabilized phosphoranes to afford the acylation products, diketo phosphoranes,21 and the occurrence of the normal Wittig reaction and the exclusive or predominant formation of the E isomers with phthalic anhydride were explained in terms of formation of a π–π complex between the C=O group of the phosphorane and the electron‐deficient benzenic ring of phthalic anhydride 20a,20c,20d. In the process of this investigation, when we realized that 3,6‐H atoms of phthalic anhydride and its analogues can form relatively strong HBs, we assumed that the H‐bonded complexes with the phosphorane can precede the Wittig reaction, and that chloroform, which is itself capable of H‐bonding, is therefore not the best choice as a solvent.…”
Section: Resultsmentioning
confidence: 99%
“…A study of the condensation of ylide 8 with unsubstituted phthalic anhydride, reported previously (6) …”
Section: -Nitrophthalic Anhydridementioning
confidence: 97%
“…Our more recent studies of the mechanism showed that condensations of cyclic anhydrides with stabilized phosphoranes lead, in a lowenergy, reversible process, to acyclic adduct(s). The enollactones are subsequently formed via a higher energy irreversible transformation ( 6 ) . Taking into account a facile reversibility of acyclic adduct(s) formation, it was not possible to determine if the initial addition products are converted to enol-lactones, or if there exists an alternate, higher energy, pathway leading directly from cyclic anhydrides to enol-lactones.…”
Section: Introductionmentioning
confidence: 99%
“…These examples highlight the importance of α-acylphosphoranes in organic synthesis. Traditionally, α-acylphosphoranes have been synthesized by acylation reaction of carboxylic acid chlorides with stabilized phosphonium ylides (Scheme , a) ,, or using carboxylic acid derivatives, ,, cyclic anhydrides, aldehydes, 1,3-dicarbonyl compounds, benzoic acid trimethylsilyl ester (TMSE), and tellurol esters . However, an efficient and simple synthesis of α-acylphosphoranes via palladium-catalyzed carbonylation under atmospheric CO pressure has received no attention.…”
mentioning
confidence: 99%